Eia ka lei: a Kānaka College Choice Framework for our survivance and ea - Chun, Nikki Lynne Mee Kāhealani, author; Poon, OiYan, advisor; Ginsberg, Ricki, committee member; Kahumoku, Walter, III, committee member; Rivera, Carmen, committee member (Colorado State University. Libraries, 2024)
This research study makes a significant contribution to understanding the experiences of Native Hawaiian students in higher education and their college choice process. Research and literature focused on or inclusive of Native Hawaiians in higher education is scarce and limited (Reyes, 2018), so there is very little known about how Native Hawaiian students navigate to and through higher education. The central research question focused on developing a college choice framework specifically tailored to Native Hawaiians: What might a college choice framework look like when developed by and for Native Hawaiians? Employing KanakaCrit (Reyes, 2018) as a theoretical framework, lei making as the research design framework (Alencastre, 2017; Vaughan, 2019), and talk story methodology (Kovach, 2010; Sing et al., 1999), the study successfully elicited stories on the college choice experiences of Native Hawaiian students. The findings led to the creation of a culturally responsive Kānaka College Choice Framework, which aims to uplift the needs and values of Native Hawaiians in college choice research and contribute to the continued survivance of the lāhui (Hawaiian nation). The framework is interdisciplinary, iterative, and integrative. Like a lei, it wraps aloha (care, love) and 'ohana (family) around the student as they navigate the college choice process.
Keywords: Kanaka critical race theory; native Hawaiian; college choice; talk story methodology; lei making